إشكالية مصطلح "الأشخاص ذوي الاحتياجات الخاصة"، والأهلية القانونية، والدمج من خلال اضطراب طيف التوحد بتطوان - Klaina, Mekki (International Journal of Education, Culture, and Society, 2025)
The condition of individuals with mental, physical, or visual disabilities, whether temporary or permanent, is an issue that requires attention and study in order to highlight its dimensions, discuss the social status of these individuals, and their ability to act based on their legal capacity. They are an integral part of society and deserve to enjoy all the rights that others benefit from, especially as their numbers continue to rise. I have chosen Autism Spectrum Disorder as a model to better understand it. This study aims to examine the appropriate term for these individuals, its historical development, and the extent to which they can perform legal actions. I have provided an example of associations working in this field, such as the Yahya Association for Children with Autism in Tetouan, Morocco. For the preparation of this research, I relied on the historical method to study the term "disability," and the analytical and critical method to study the social behavior with this group, as well as to analyze the legal texts related to them. In this study, I emphasized the need to pay attention to the words used when talking about them, their right to full inclusion, and the necessity of granting them legal capacity.